ASSESSMENT OF SUSTAINABLE TOURISM USING SOCIAL, ECONOMIC, AND ENVIRONMENTAL INDICATORS: CASES STUDY OF BANJARNEGARA, INDONESIA - Sukmawati, Enra Riesti; Niyommaneerat, Wilailuk; Sakcharoen, Thammananya (UI Scholars Hub, 2022)
Sustainable tourism requires valuable and useful resources, balances people's social, economic, and environmental goals, and realizes the carrying capacity of resources. This paper examines the tourism situation in the City of Banjarnegara, Central Java, Indonesia, using the three pillars of sustainable tourism: Social, Economic and Environmental. This study aims to examine sustainable tourism in Banjarnegara by following indicators from the Global Council on Sustainable Tourism Destinations Criteria (GSTC-D) and publications in international journals using the keyword